2015
DOI: 10.1261/rna.053793.115
|View full text |Cite
|
Sign up to set email alerts
|

Functional relevance of “seed” and “non-seed” sequences in microRNA-mediated promotion of C. elegans developmental progression

Abstract: The founding heterochronic microRNAs, lin-4 and let-7, together with their validated targets and well-characterized phenotypes in C. elegans, offer an opportunity to test functionality of microRNAs in a developmental context. In this study, we defined sequence requirements at the microRNA level for these two microRNAs, evaluating lin-4 and let-7 mutant microRNAs for their ability to support temporal development under conditions where the wild-type lin-4 and let-7 gene products are absent. For lin-4, we found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 72 publications
(128 reference statements)
0
15
2
Order By: Relevance
“…Loss of let-7 results in a lethal phenotype where animals burst through their vulvas (Reinhart et al, 2000; Slack et al, 2000), and this phenotype can be suppressed by restoring regulation of just lin-41 (Ecsedi et al, 2015). Additionally, versions of let-7 that contain mutations in 3′ end sequences do not fully rescue bursting of let-7 mutants, pointing to the importance of the 3′ end of this miRNA (Zhang et al, 2015). To further test if regulation of lin-41 is entirely dependent on let-7, we analyzed the expression of lin-41 in let-7(n2853) animals and in null mutants of miR-48 and miR-241, at mid-L4 stage.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of let-7 results in a lethal phenotype where animals burst through their vulvas (Reinhart et al, 2000; Slack et al, 2000), and this phenotype can be suppressed by restoring regulation of just lin-41 (Ecsedi et al, 2015). Additionally, versions of let-7 that contain mutations in 3′ end sequences do not fully rescue bursting of let-7 mutants, pointing to the importance of the 3′ end of this miRNA (Zhang et al, 2015). To further test if regulation of lin-41 is entirely dependent on let-7, we analyzed the expression of lin-41 in let-7(n2853) animals and in null mutants of miR-48 and miR-241, at mid-L4 stage.…”
Section: Resultsmentioning
confidence: 99%
“…It could be possible that miR-34a-3p directly or indirectly downregulates MMP2 activity. It must be observed that MMP2 does not have binding sites for the 3p strand of miR-34a-3p; nevertheless, several miRNAs regulate mRNAs independently of the seed sequence [71].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA regulation strength in animals is greatly dependent on the amount of complementarity between miRNA seed region (a domain at the 5′ end of miRNA transcripts that spans from nucleotide position 2 to 7) and MRE at the mRNA transcript. However, there is growing evidence that the downstream nucleotides of miRNAs may also play a relevant role 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%